World Experience of the Public-Private Partnership and Challenges of its Implementing in Ukraine - Olentsevych, N.V.; Kovalyova, O.V (Економічний вісник Донбасу, 2014)
Introduction. The implementation of the public-private partnership in Ukraine is becoming vital to the tackling financial challenges of the construction and operation of asserts of the strategic importance for providing socio-economic development of the society in an environment of budget shortfalls.The analysis of a foreign experience in the realization of the partnership between public and private sectors allows us to organize guidance and conditions of the PPP implementation for further use in Ukraine.Purpose. Generalization of the experience of the public-private partnership implementing in the developed countries and development of proposals for the public-private partnership realization in Ukraine. Method (methodology). The Comparative analysis of the practice of the realizing public-private partnership in the UK, France, the USA, the Netherlands. Results. On the basis of the public-private practice research in the developed European countries and the United States of America the special features of the establishment of national models and specific form of public-private partnership have been determined. Evolutionary changes in the performing the governmental functions and constructing the partnership system in the sphere of participant diversification and increasing the transparency and efficiency of projects have been traced. It was proved that the quantitative and qualitative leap in the public-private partnership development in the countries studied pertained to the establishment of the special public agencies and institutions to hold consultations, economic expertise and facilitated the introduction of the collaboration between government and business. Priority forms and areas of public-private partnership implementation in the countries studied have been defined. The main obstacles to the realization of long-term public-private partnership forms in Ukraine related to the political turmoil, absence of state guaranties and high risks of making investment have been revealed. The necessity to improve the staffing capacity of the public-private partnership implementation process and development appropriate methodology documentation has been proved. It was concluded that there is a need to create a special institution to coordinate the implementation of the partnership between the state and business in Ukraine and improve the legal framework for the regulation of public-private partnerships at the local and national levels. На основі дослідження світової практики здійснення державно-приватного партнерства виявлено особливості становлення національних моделей та окремих форм реалізації державно-приватного партнерства в провідних європейських країнах і США. Систематизовані еволюційні зміни у здійсненні функцій держави та обґрунтовано необхідність побудови системи партнерських відносин у напрямку диверсифікації учасників, забезпеченні прозорості та ефективності реалізованих проектів. Аргументовано положення про те, що якісний і кількісний стрибок у розвитку державно-приватного партнерства забезпечується шляхом створення необхідних інституційних передумов і форм - спеціальних установ і інституцій для здійснення консультацій, економічної експертизи та сприяння становленню співпраці держави і бізнесу. Виявлено основні проблеми та пріоритетні напрямки здійснення державно-приватного партнерства в Україні в довгостроковій перспективі. На основе исследования мировой практики осуществления государственно-частного партнерства выявлены особенности становления национальных моделей и отдельных форм реализации государственно-частного партнерства в ведущих европейских странах и США. Систематизированы эволюционные изменения в осуществлении функций государства и обоснована необходимость построения системы партнерских отношений в направлении диверсификации участников, обеспечении транспарентности и эффективности реализуемых проектов. Аргументировано положение о том, что качественный и количественный скачок в развитии государственно-частного партнерства обеспечивается путем создания необходимых институциональных предпосылок и форм - специальных учреждений и институтов для осуществления консультаций, экономической экспертизы и содействия становлению сотрудничества государства и бизнеса. Выявлены основные проблемы и приоритетные направления осуществления государственно-частного партнерства в Украине в долгосрочной перспективе.